Hubungan Faktor Demografi dengan Durasi Pre-Hospital pada Pasien Stroke Akut di RSUD Abdoel Wahab Sjahranie - Yetty Hutahaean (PERDOSNI, 2026)
Introduction: The pre-hospital period plays a critical role in determining the outcomes of patients with acute stroke. Various demographic factors can influence the time at which a patient arrives at the hospital.Aim: This study aims to examine the correlation between demographic factors and the duration of prehospital stay in acute stroke patients at Abdoel Wahab Sjahranie Samarinda Regional Public Hopsital (RSUD).Methods: The research design employed int this study was observational and analytical, utilizing a cross-sectional methodology. Data for the study were collected through interviews with the patients’ family members and by reviewing their medical records. The sample consisted of 80 participants who met the inclusion criteria, , including 61 patient with ischemic stroke and 19 patients with hemorrhagic stroke.Results: The findings of the study revealed that the average age of acute stroke patients was 63, with a majority of them being male. Most of the individuals who experienced acute strokes had completed high school education. In comparison to those who were unemployed, a higher percentage of acute stroke patients were employed and earned more than minimum wage. All 80 acute stroke patients had health insurance coverage. The majority of acute stroke patients did not own cars and resided within a 10-kilometer radius of the hospital. The study found no significant correlation between the duration of pre-hospital in acute stroke patients and factors such as age, gender, education level, occupation, income or car ownership (p = 0.246 ; 0.174 ; 0.515 ; 0.475 ; 0.769 ; 0.771).Discussion: It was observed that the distance of the patient’s residence from the hospital (>10 km) was associated with delayed hospital arrival in acute stroke patients, with a p-value of 0.008.Keywords: : Acute Stroke, Demographic, Pre-hospital